Pengaruh Kepemimpinan Partisipatif, Motivasi Kerja, Disiplin Kerja, Dan Lingkungan Kerja Terhadap Kinerja Pengawai Pada Sekretariat Dewan Perwakilan Rakyat Daerah ( DPRD ) Kabupaten Alor - Samny Felederik Bely (Peneliti.net, 2023)
Performance is the result of work achieved by employees based on job requirements. A job has certain requirements so that it can be carried out to achieve goals which are also known as work standards. The results of work are things that are obtained by an employee in carrying out the work according to the requirements or performance standards. An employee is said to be successful in carrying out his work or having good performance, if the work results obtained are higher than the performance standards. To know this, it is necessary to evaluate the performance of each employee in an agency. Performance problems certainly can not be separated from the process results and usability. Performance itself means a work result that can be achieved by a person or group of people in an organization, according to their respective authorities and responsibilities, in order to achieve organizational goals. This study aims to determine the effect of participatory leadership, work motivation, work discipline and work environment on employee performance. The population and sample in this study were employees at the Secretariat Office of the Regional People's Representative Council (DPRD) of Alor Regency, totaling 37 people. The sampling technique in this study is saturated sampling. The statistical method used in this research is multiple linear regression. This type of research is quantitative research with data collection techniques, namely observation, interviews, and documentation studies. The results of this study indicate that: (1). partially the participatory leadership variable has a significance value of 0.000 or 2.3% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H1 which states that the Participatory Leadership variable partially has a positive effect on employee performance at Alor Regency Regional People's Representative Council (DPRD) Secretariat Office. (2). partially the work motivation variable has a significant value of 0.000 or 0.00% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H2 which states that the work motivation variable partially has a positive effect on employee performance. at the Secretariat Office of the Regional People's Representative Council (DPRD) of Alor Regency (3). Partially the work discipline variable has a significant value of 0.001 or 0.1% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H3 which states that the work discipline variable partially has a positive effect on employee performance in Alor Regency Regional People's Representative Council (DPRD) Secretariat Office. (4). partially the work environment variable has a significant value of 0.000 or 0.0% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H4 which states that the variable work discipline partially has a positive effect on employee performance at Secretariat Office of the Regional People's Representative Council (DPRD) Alor Regency (5). simultaneously the participatory leadership variable work motivation work discipline and work environment has a significant value of 0.000 or 0.00% where this value is smaller than the alpha value which is equal to 0.05 which is 5% so that the results of this study simultaneously receive H5 which states that the variable participative leadership, work motivation, work discipline and work environment simultaneously have a positive effect on employee performance at the Secretariat Office of the Regional People's Representative Council (DPRD) of Alor Regency. (6). The magnitude of the influence of participatory leadership variables on work motivation, work discipline and work environment is 70.4%, this study simultaneously accepts H5.